The Use of Recycled Material-Based Educational Play Tools (APE) to Improve Fine Motor Skills - Dian Irmasari; Septyana Tentiasih (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the effectiveness of using recycled-material Educational Play Tools (APE) in improving early childhood fine motor skills. The background of this study is the low ability of children in activities such as cutting, pasting, and threading, as well as the suboptimal use of creative learning media. The study employed a quantitative approach with a quasi-experimental design using a One Group Pretest-Posttest model involving 12 children aged 3–4 years. Data were collected through observation, performance assessment, and documentation, and then analyzed using descriptive quantitative techniques. The results showed a significant improvement, indicated by an increase in percentage from 25% to 83.3%. Improvements were observed in cutting, pasting, threading, and hand-eye coordination skills. These findings indicate that recycled-material APE is effective, innovative, and environmentally friendly, and can serve as an alternative learning medium to optimally support children’s fine motor development.